Effect of age and environmental factors on insulin release from the perfused pancreas of the rat. - Reaven, E (1983)
In this study we examined the effect of age and various age-related environmental factors on maximal glucose-stimulated insulin release by the intact perfused pancreas. Male Sprague-Dawley rats were maintained from 40 d to 12 mo of age on standard chow, or on a sucrose-rich or calorie-restricted diet. At 12 mo, studies were carried out on the isolated pancreas of each animal to determine maximal (300 mg/ml) glucose-stimulated insulin secretion. After these studies were completed, each pancreas was perfused with formalin fixative and processed for morphometric estimation of the mass of the endocrine pancreas. Data from these older animals were compared with data from 2-mo-old control rats. The results indicate that maximal glucose-stimulated insulin secretion per unit endocrine pancreas was markedly reduced in all three groups of 12-mo-old rats, and was only 25-33% of that of 2-mo-old rats. Thus, aging led to a decline in insulin secretion per beta cell that was not modifiable by environmental manipulation. On the other hand, environmental factors can influence the development of endocrine tissue within the pancreas, and in so doing, modify total pancreatic insulin secretion. The mass of the endocrine pancreas of 12-mo-old rats fed either sucrose or chow was between three and four times that of 2-mo-old control rats, and these older rats were able to maximally secrete as much insulin per total pancreas as the young rats. In contrast, the endocrine cell mass of the calorie-restricted rats had not enlarged to this extent, and the maximally stimulated perfused pancreas from these rats secreted less insulin. These data suggest that the aging animal, challenged in vivo to secrete insulin, can overcome the loss of the beta cell response by expanding its pancreatic pool of beta cells. Although this compensation is successful in the 12-mo-old, obese, middle-aged rat, it is not yet clear what effect further aging would have on these events.